Student’s Environmental Literacy Profile SMPN 1 Pekalongan - Ikasari Dewi; Fenny Roshayanti; Endah Rita Sulistya Dewi (Quagga: Jurnal Pendidikan dan Biologi, 2024)
Education is one effort to overcome environmental problems. This effort needs to start by knowing the profile of students. This research aims to determine the literacy profile of students at SMP N 1 Pekalongan. This research is a type of qualitative descriptive research. The sample in this study was 122 students from class VII. This research indicator refers to NELA, an environmental literacy assessment project implemented in the United States. The data collection technique is through tests using the Middle School Environmental Literacy Survey (MSELS). The test includes four indicators, namely: ecological knowledge, environmental problem-solving skills, attitudes and concern for the environment, and environmentally responsible behavior. Research data was analyzed descriptively based on achievement value criteria. The results of the research show that the environmental literacy level of students at SMP N 1 Pekalongan is 57.32, which is categorized as medium. The ecological knowledge indicator is 50.24 (fair), environmental problem-solving skills is 43.77 (fair), attitude and concern for the environment is 66.25 (good) and environmentally responsible behavior is 69.04 (good). Efforts need to be made so that students' environmental literacy at SMP N 1 Pekalongan in each indicator reaches the outstanding category.